Trophic ecology of detritivorous fish along a reservoir cascade in a tropical semi-arid region - de Oliveira, Jean Carlos Dantas; de Oliveira, Jonnata Fernandes; Marques, Alexandre de Oliveira [UNESP]; Peretti, Danielle; da Costa, Rodrigo Silva; Novaes, José Luís Costa (Wiley, 2021)
The objectives of this study were to investigate the food resources consumed by two species of detritivorous fishes along the Apodi-Mossoró River reservoir cascade system, located in the tropical semi-arid region of Brazil. The hypotheses tested were as follows: (a) the diet, niche breadth and niche overlap of the species in the reservoirs downstream of the cascade are different due to the blockage of food resources upstream, and (b) the two species coexist in the reservoir cascade system due to resource partitioning. The diets of the species were analysed based on the volumetric data of the food resources using NMDS ordination, and possible differences in diet were tested with PERMANOVA. The contribution of each food resource was analysed by SIMPER analysis. Trophic niche breadth was evaluated by PERMDISP analysis, and the trophic niche overlap was calculated by the Pianka index. The difference in niche overlap between the reservoirs was evaluated by Welch's t test. Plant material, detritus and sediment were the most important food resources in the diets of the two species, but they differed along the reservoir cascade. Plant material, detritus and sediments were the predominant resources in their diets, which showed differences in feeding, a narrow trophic niche and high dietary overlap. The differences in diet observed along the cascade did not follow the expected pattern, and the narrow trophic niche and high trophic overlap indicate that the sharing of food resources was not the main cause of the coexistence of these species in the reservoirs.
Keywords: diet; hydrological connectivity; intermittent river; trophic niche